Retrospective study on laparoscopic hysterectomy by vaginal vault closure method in a tertiary care centre - Ganiga, Pradeep; B., Divyashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hysterectomy is the frequently performed operation for benign conditions of uterus, but the route of hysterectomy is always a matter of discussion. Laparoscopic hysterectomy is an expensive and time-consuming procedure and could be associated with increased risk of thermal damage related injuries to the surrounding structures. Presently, laparoscopic hysterectomy is considered to be a day care surgery because of technological improvement in electro-surgical unit and expertise of doing surgery. The objective of this study was as a retrospective observational study conducted in teaching hospital to study the factors like age, parity, indication and procedure related complications in detail. Methods: A total number of 40 patients who have undergone laparoscopic hysterectomy for various indications with vault closure by vaginal method with no. 1 PDS. A detailed analysis of cases was done according to age, parity, indication, intra-operative and post-operative outcomes. Results: Fibroid uterus was the most common indication for laparoscopic hysterectomy. Overall postoperative complication rate was 22.5% with no major morbidity reported. Conclusions: Laparoscopic hysterectomy has to be done with proper selection of patient and good peri-operative care. Vault closure by vaginal method has significantly reduced operating time, without increasing the morbidity.